Analisis Dimensi Kualitas Layanan Akademik Berdasarkan Persepsi Mahasiswa Program Studi Manajemen Dakwah - Agus Wahyu Triatmo; Ade Yuliar (Jurnal Matlamat Minda : Manajemen Dakwah, 2022)
This study aims to determine student perceptions of the quality of academic services in the Department of Da'wah Management Faculty of Ushuluddin and Da'wah UIN Raden Mas Said Surakarta. The determination of the object of this study is based on convenience sampling. This research is a quantitative descriptive study with multiple case study approach. The conclusion of this study shows that in general, students' perceptions of the quality of academic services viewed from aspects of tangibles, reliability, responsiveness, assurance and empathy are quite good. However, there are still weaknesses including those related to aspects of adequate infrastructure and improvement of the ability of lecturers in teaching. In addition, the response of the department leadership in terms of service to students to be improved.